PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE WORD SQUARE TERHADAP SIKAP BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XI IPS DI SMA NEGERI 9 KOTA JAMBI - Resi Adelina Manullang, Tri Wahyuni, (Universitas Batanghari Jambi, 2018)
AbstractThis study aims to determine the description of respondents and the influence of the use of cooperative learning model type word square on student learning attitudes on economic subjects class XI IPS in SMA Negeri 9 Kota Jambi. Based on the data analysis on the results of research that there is a significant influence between the use of cooperative learning model type word square on student learning attitudes on economic subjects class XI IPS in SMA Negeri 9 Kota Jambi. The results showed that (1) students' learning attitudes using cooperative learning model type Word Square on Economics class XI IPS In SMA Negeri 9 Kota Jambi is quite good. It is indicated by the average of students 'learning attitudes in the experimental class is 3.86 with the TCR of 77.11, and (2) the use of cooperative learning model of Word Square type significantly influence the students' attitude on the subjects of Economics class XI IPS in SMA Negeri 9 Kota Jambi. This is indicated by the value of thitung> ttable (13,48> 2,03693). Keyword : Word Square Learning Model, Learning Attitude.